2013
DOI: 10.1152/ajprenal.00706.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAPK attenuates renal atrophy and fibrosis in a murine renal artery stenosis model

Abstract: Renal artery stenosis (RAS) is an important cause of chronic renal dysfunction. Recent studies have underscored a critical role for CCL2 (MCP-1)-mediated inflammation in the progression of chronic renal damage in RAS and other chronic renal diseases. In vitro studies have implicated p38 MAPK as a critical intermediate for the production of CCL2. However, a potential role of p38 signaling in the development and progression of chronic renal disease in RAS has not been previously defined. We sought to test the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 51 publications
6
42
0
Order By: Relevance
“…MAPK signaling pathway is a classical signaling pathway, which can be activated by various factors including TGF-b1 [37]. Studies demonstrate that MAPK signaling pathway regulates cell apoptosis and is involved in tubular injury, and MAPK signaling inhibition can prevent apoptosis of tubular cells [18,38]. EGCG is reported to modulate MAPK signaling in various types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathway is a classical signaling pathway, which can be activated by various factors including TGF-b1 [37]. Studies demonstrate that MAPK signaling pathway regulates cell apoptosis and is involved in tubular injury, and MAPK signaling inhibition can prevent apoptosis of tubular cells [18,38]. EGCG is reported to modulate MAPK signaling in various types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway is a classic signaling pathway that regulates cell apoptosis and inflammation and is involved in serious tubular injury (Qin et al, 2012;Zheng et al, 2012;Wang et al, 2013). Qin et al (2012) reported that A. membranaceus, from which AS-IV is purified, inhibited the phospho-p38 MAPK pathway in advanced glycation endproduct-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…29) Inhibition of p38 MAPK can attenuate renal and lung fibrosis. 23,30,31) In addition, p38 MAPK plays an important role in CF proliferation. 32,33) In this study, CFs showed a significant increase in p38 phosphorylation when treated with ISO, as compared with untreated controls.…”
Section: Discussionmentioning
confidence: 99%